A cluster of constitutive mutations affecting the C-terminus of the redox-sensitive SoxR transcriptional activator. - Nunoshiba, T (1994)
Activation of Escherichia coli oxidative stress regulon genes (sodA, zwf, fumC, nfo, etc.) is mediated by a two-stage regulatory system: the redox-sensitive SoxR protein transcriptionally activates the soxS gene, whose product then stimulates transcription of the regulon genes. Previous experiments showed that limited 3' truncation of soxR gene causes constitutive soxRS expression. DNA sequence analysis of the soxR genes from the soxRS-constitutive strains isolated originally (Greenberg et al. (1990) Proc. Natl. Acad. Sci. USA 87, 6181-6185) revealed that three alleles encode amino acid substitutions or a chain termination clustered near the C-terminus of SoxR. Two other single-amino-acid substitutions in constitutive alleles mapped to the helix-turn-helix motif and to a region of unknown function in the center of the polypeptide, respectively. No constitutive mutation was found within the region encoding the cysteines of the SoxR FeS center, in the soxR or soxS promoters, or in the soxS structural gene. Since an in-frame deletion of just nine SoxR residues (136-144; full-length SoxR = 154 residues) gave rise to a powerful constitutive allele, it appears that a small segment of the SoxR C-terminus maintains the protein in the inactive state. Conservely, an intact C-terminus is evidently not required for gene activation by SoxR.